Separate origins of group I introns in two mitochondrial genes of the katablepharid Leucocryptos marina. - Yuki Nishimura (Public Library of Science (PLoS), 2012)
Mitochondria are descendants of the endosymbiotic α-proteobacterium most likely engulfed by the ancestral eukaryotic cells, and the proto-mitochondrial genome should have been severely streamlined in terms of both genome size and gene repertoire. In addition, mitochondrial (mt) sequence data indicated that frequent intron gain/loss events contributed to shaping the modern mt genome organizations, resulting in the homologous introns being shared between two distantly related mt genomes. Unfortunately, the bulk of mt sequence data currently available are of phylogenetically restricted lineages, i.e., metazoans, fungi, and land plants, and are insufficient to elucidate the entire picture of intron evolution in mt genomes. In this work, we sequenced a 12 kbp-fragment of the mt genome of the katablepharid Leucocryptos marina. Among nine protein-coding genes included in the mt genome fragment, the genes encoding cytochrome b and cytochrome c oxidase subunit I (cob and cox1) were interrupted by group I introns. We further identified that the cob and cox1 introns host open reading frames for homing endonucleases (HEs) belonging to distantly related superfamilies. Phylogenetic analyses recovered an affinity between the HE in the Leucocryptos cob intron and two green algal HEs, and that between the HE in the Leucocryptos cox1 intron and a fungal HE, suggesting that the Leucocryptos cob and cox1 introns possess distinct evolutionary origins. Although the current intron (and intronic HE) data are insufficient to infer how the homologous introns were distributed to distantly related mt genomes, the results presented here successfully expanded the evolutionary dynamism of group I introns in mt genomes.